Challenges in implementing an integrated environmental management approach in Zimbabwe - Rajah, Naome,; Rajah, Dino; Jerie, Steven (Scholarlink Resource Centre, 2016)
This paper attempts to specifically identify the problems and challenges of environmental legislation in Zimbabwe and the need, for implementing an integrated approach to managing the environment. The researcher commissioned a survey in which 100 respondents comprising institutional heads, local leaders, farmers, communal and urban settlers were selected. These were served with questionnaires. Follow up interviews, direct observations and documentary reviews were also employed in collecting the data that is presented. After a thorough analysis of the data, major findings emerged from which conclusions were drawn in that the legislation before EMA was fragmented and outdated. Whilst EMA is punitive to some degree, it lacked adequate human and financial resources to enforce it. Furthermore there was partial integration of the various statutes which guided the management of natural resources in a holistic manner. The study recommends the need for a cohesive and appropriate environmental management delivery strategy that calls for an integrated approach with enough institutional support, funding and administration to ensure successful implementation. The effectiveness of environmental law in Zimbabwe is seen by the success and failure in providing environmental justice, fostering public participation and ensuring that legislation adequately protects the environment from pollution and degradation. In Zimbabwe, sustainable management is the law of the land; it is also the law of the water, the air, the wildlife, the heritage, buildings and culture